Close encounters with foreignness. Issue 2 (4th May 2019) - Bennett, Bruce; Marciniak, Katarzyna
ABSTRACT: This article opens with reflections upon the authors' formative encounters with world cinema in Poland and the UK, and the importance of television in providing access to a wide variety of 'foreign' films. We propose that the process of viewing transnational films exemplifies this encounter with foreignness and that the value of studying transnational films is that their thematic focus upon encounters invites us to reflect upon questions of translation and misrecognition, difference and sameness. Through a close analysis of Cold War (Pawlikowski, 2017), the article discusses the way in which this film explores questions of cultural politics and national identity, migrant experience and exile, and the transnational circulation of texts. We argue that the film, which follows the experiences of a couple who move back and forth across the 'iron curtain' in post-WW2 Europe, offers a critique of nationalist ideologies and invites us to recognise 'foreignness' as a constitutive component of local and national cultures. Cold War, we suggest, is an exemplary transnational film in so far as it prompts us to recognise how even familiar cultures are repeatedly transected by difference.